Serum solubl-lL-2 receptor levels in patients with chronic liver disease - Hakan YÜCEYAR; Ali KOKULUDAĞ; Ömer ÖZÜTEMİZ and Ahmet KESKİNOĞLU and Tomris KABAKÇI and Filiz SEBİK and Yücel BATUR (Turkish Journal of Gastroenterology, 2020)
-